düï ëítr ŵŷ
Step-by-step explanation:
sfëk£ï ãdjd
Answer:
4a³+3a-3
Step-by-step explanation:
You can solve this by combining like terms. Add the numbers with the correct exponents together.
-a³+5a³
4a-a
Thus, the answer is
4a³+3a-3
Answer:
53
Step-by-step explanation:
Answer:
24m - 28
Step-by-step explanation:
Given the expression (6m−7)⋅4, we are to simplify it. Using the distributive law;
A(B+C) = AB + AC [A is distributed over B and C]
For the expression (6m−7)⋅4, we will distribute 4 over 6m and -7 as shown;
(6m−7)⋅4 = 4(6m) - 4(7)
(6m−7)⋅4 = 24m - 28
Hence (6m−7)⋅4 = 24m - 28
Total surface area of first box = 2(8 * 6.25) + 2(8 * 10.5) + 2(6.25 * 10.5) = 2(50) + 2(84) + 2(65.625) = 100 + 168 + 131.25 = 399.25 sq. ins
Total surface area of second box = 2(9 * 5.5) + 2(9 * 11.75) + 2(5.5 * 11.75) = 2(49.5) + 2(105.75) + 2(64.625) = 99 + 211.5 + 129.25 = 439.75 sq. ins
Hence, the second box requires more material to make.